SUSTAINABLE MORTGAGE FINANCING MODEL FOR INFORMAL WORKERS USING A DIGITAL ECOSYSTEM AND COMMUNITY-BASED APPROACH - Hadi Purnomo (SEAN Institute, 2022)
The fulfillment of decent and cheap housing for the community is in line with the Sustainable Development Goals (SDGs). The Indonesian government has committed to achieved the SDGs target through the provision of subsidized housing loans. The purpose of this research is to analyze the problematic situation and formulate a plan to improve the housing loans model for the poor and informal workers. The model was built using the Soft System Methodology (SSM) approach. This study shows that the hybrid housing loans model and the hybrid housing loans community-based model can be developed into a solution to the problem. These schemes have resulted in a synergy between PT Sarana Multigriya Finansial (SMF) as secondary mortgage company that collaborates with companies in digital ecosystem and community-based company. The implications based on the findings of this study indicate that both new housing loans scheme can reduce the risk of housing loans as well as accelerate the approval process